Factors Predicting Uterine Rupture Following a Cesarean Section - Shehla Tabassum; Bushra Khan; Hina Zahra Qureshi; Humaira Imran (Life and Science)
Objective: This study was conducted to evaluate factors that predict uterine rupture following a previous cesarean section. Study Design: A cross-sectional study. Place and Duration of Study: The Study was conducted at the Department of Gynecology, Bakhtawar Amin Hospital Multan, Pakistan from June 2022 to June 2023. Methods: The study included 100 women who had previously given birth. Women who had a successful vaginal birth after cesarean section (VBAC) were controls and who had rupture/scar dehiscence were considered cases. Socio-demographic data and information related to delivery, labor, and pregnancy were collected. Results: A total of 100 women (40 cases and 60 controls) were included in the study. All women had spontaneous onset of labor. 12.5% (8) cases and 85% (51) controls had a successful vaginal birth after the cesarean section (VBAC). 34.1% of all rupture cases happened during the second stage of labor and 41.4% during the latent phase of labor. Upon arrival 30% (12) of cases had shock. Maternal complications in cases included anemia (21 patients), death (2 patients), uterine artery involvement (3 patients), and bladder rupture (4 patients). According to multivariate analysis factors including previous vagina delivery, duration of labor, fetal weight, and number of ANC visits were significantly related to rupture of uterus after previous cesarean (P<.05). Conclusion: Factors including prolonged labor, lesser antenatal care follows ups, and fetal weight > 3.8 kg increase the likelihood of uterine rupture following a C-section. It is crucial to develop strict criteria, considering intrapartum obstetric care, infrastructure, and referral system, for the selection of favorable candidates for trial of labor.